Angiogenic Effects of Extracellular Human Immunodeficiency Virus Type 1 Tat Protein and Its Role in the Pathogenesis of AIDS-Associated Kaposi's Sarcoma - Barillari, Giovanni (American Society for Microbiology, 2002)
The Tat protein of human immunodeficiency virus (HIV) type 1 is a transactivator of viral gene expression that is required for virus replication and spread. Moreover, Tat is released by acutely HIV-infected cells via a leaderless secretory pathway and in a biologically active form that exerts effects on both HIV-infected and uninfected cells from different organs and systems. This review focuses on the activities of extracellular Tat protein on endothelial cells, on angiogenesis, and on the pathogenesis of AIDS-associated angioproliferative diseases such as Kaposi's sarcoma. In particular, we discuss results from different groups indicating that Tat mimics the proangiogenic activities of extracellular matrix molecules and that it enhances the effects of angiogenic factors.